2014
DOI: 10.1002/anie.201407717
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed Highly Diastereo‐ and Enantioselective Alkyne Oxidation/Cyclopropanation of 1,6‐Enynes

Abstract: A highly enantioselective oxidative cyclopropanation of 1,6-enynes catalyzed by cationic Au(I)/chiral phophoramidite complexes is presented. The new method provides convenient access to densely functionalized bicyclo[3.1.0]hexanes bearing three contiguous quaternary and tertiary stereogenic centers with high enantioselectivity (up to e.r. 98:2). Control experiments suggest that the quinoline moiety of the β-gold vinyloxyquinolinium intermediate in the reaction plays an important role in promoting good enantios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(46 citation statements)
references
References 66 publications
2
43
0
1
Order By: Relevance
“…Several examples of tandem oxidative carbene complex generation and intramolecular cyclopropanation were reported using gold catalysts featuring rigid P,N-bidentate ligands [1215]. An enantioselective intramolecular cyclopropanation process was observed upon treatment of alkynyl ketones that contain pendant alkene groups with a PNO and a cationic gold complex containing various chiral phosphine ligands [1216]. The reaction of terminal alkynes with gold catalysts in the presence of a PNO and a sulfonic acid derivatives led to β-ketosulfonate esters in a process where the initially-generated carbene complex reacts with the sulfonic acid to afford the net O-H insertion product [1217].…”
Section: Scheme 101 Formation Of Ring-fused Cyclopropanes Using Metamentioning
confidence: 99%
“…Several examples of tandem oxidative carbene complex generation and intramolecular cyclopropanation were reported using gold catalysts featuring rigid P,N-bidentate ligands [1215]. An enantioselective intramolecular cyclopropanation process was observed upon treatment of alkynyl ketones that contain pendant alkene groups with a PNO and a cationic gold complex containing various chiral phosphine ligands [1216]. The reaction of terminal alkynes with gold catalysts in the presence of a PNO and a sulfonic acid derivatives led to β-ketosulfonate esters in a process where the initially-generated carbene complex reacts with the sulfonic acid to afford the net O-H insertion product [1217].…”
Section: Scheme 101 Formation Of Ring-fused Cyclopropanes Using Metamentioning
confidence: 99%
“…Michelet and coworkers applied this reaction to the synthesis of tetrahydrofurans with modest enantioselectivities using indoles, 1,3,5-trimethoxybenzene and water as nucleophiles [101]. Although containing only one example of an enantioenriched heterocycle, 8-methylquinoline N-oxide has also been used to form a ketone-functionalized lactam using a similar strategy [102].…”
Section: Intramolecular Cyclizationsmentioning
confidence: 99%
“…The oxidant we use was an N -oxide, which is mild, [13], [14] hence, we expected good functional group tolerance. We recently demonstrated that excess amounts of silver salt in gold catalysis almost always had a deleterious effect on the reactivity of gold catalysts and that a preformed gold catalyst like L-Au-NTf 2 , usually exhibited the best reactivity.…”
mentioning
confidence: 99%